Human-AI in affordance perspective: a study on ChatGPT users in the context of Indonesian users - Haqqu, Rizca; Zahrani, Alya Rahma; Wulandari, Astri; Ersyad, Firdaus Azwar; Adim, Adrio Kusmareza (Frontiers in Computer Science, 2025)
This study explores the interaction between humans and artificial intelligence (AI) through the lens of affordance theory, focusing on how Indonesian users experience and interpret ChatGPT in their daily lives. Adopting a socioconstructivist approach to affordance, the research investigates how users perceive, adapt to, and assign meaning to ChatGPT’s capabilities beyond its technical design. Using a qualitative descriptive method with light netnographic observation, this study examines user interactions and discussions within online communities. The findings reveal that affordances are not solely embedded in the AI system but emerge relationally, shaped by users’ intentions, contexts, and social interpretations. ChatGPT is variously perceived as a thinking assistant, productivity enhancer, confidence booster, and reflective partner. These perceptions are informed by diverse user motivations, such as improving work efficiency, overcoming cognitive barriers, or seeking emotional support in moments of solitude. The study identifies a dynamic interaction between technological features and human agency, highlighting how users’ lived experiences co-construct the functional and symbolic value of AI. This research contributes to the evolving discourse on human–AI relationships by emphasizing the subjective and socially situated nature of affordances, offering insights into how users domesticate AI tools in everyday contexts. Ultimately, the study challenges deterministic views of technology by demonstrating that the perceived value of AI is co-created through experiential engagement rather than solely defined by its technical affordances.